2012
DOI: 10.2478/v10078-012-0051-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rhythm Training on Tennis Performance

Abstract: Rhythm training is an integral part of sports. The purposes of the study were to analyze the effects of rhythm training on tennis performance and rhytmic competence of tennis players, to compare the improvement levels of tennis specific and general rhythm training and to examine the effects of shorter and longer tempos on rhythmic competence. Thirty university students whose mean score of International Tennis Number (ITN) was 7.3 (±0.9) were divided randomly into three sub-groups: Tennis Group, General Rhythm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
8

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
2
9
0
8
Order By: Relevance
“…The SMT group showed a significant, increasing number of correct foot taps and took on average a shorter time to complete the stepping task at the post-test in comparison to the pre-test. These results add to previous findings of improvement in outcome accuracy as an effect of SMT found on golfers’ performance (Libkuman et al, 2002; Sommer and Rönnqvist, 2009); reduced variability and enhanced precision of soccer cross-passes in soccer players (Sommer et al, 2018); and to findings from similar timing training programs that have reported associations between rhythmic competences and improved tennis performance (Sogut et al, 2012).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The SMT group showed a significant, increasing number of correct foot taps and took on average a shorter time to complete the stepping task at the post-test in comparison to the pre-test. These results add to previous findings of improvement in outcome accuracy as an effect of SMT found on golfers’ performance (Libkuman et al, 2002; Sommer and Rönnqvist, 2009); reduced variability and enhanced precision of soccer cross-passes in soccer players (Sommer et al, 2018); and to findings from similar timing training programs that have reported associations between rhythmic competences and improved tennis performance (Sogut et al, 2012).…”
Section: Discussionsupporting
confidence: 84%
“…For example, Massad has described how the IM training program has been used and praised by top PGA tour golfers, American football team Notre Dame , and NBA team Miami Dolphins . In line with these findings, both general rhythm training and tennis specific rhythm training have been described to have an effect on both rhythmic competences as well as on tennis performance in tennis players (Sogut et al, 2012). Although there are many reports from different sports teams and coaches that the IM training program is effective, there are still a limited number of scientific research publications on the relationship between SMT and athletic performance.…”
Section: Introductionsupporting
confidence: 52%
“…Thus, whereas timing in imagery corresponds to the duration or speed of a global task, rhythmicity relates to the relative timing of different parts of a task, such as when a series of co-ordinated actions are performed. Links have been shown between rhythmicity and performance of a number of sports including gymnastics (Pica, 1998 ), golf (Kim et al, 2011a ), dance (Laurence, 2000 ), fencing (Borysiuk and Waskiewicz, 2008 ), swimming (Zachopoulou et al, 2000 ) and tennis (Sogut et al, 2012 ). Rhythm, like imagery, is an important component in ensuring effective preparation for competition (MacPherson and Collins, 2009 ).…”
Section: Rhythmicitymentioning
confidence: 99%
“…Duvar çalışmalarında ritim çok önemlidir ve doğru antrenman programı ile hızlı ve etkili gelişme kaydedilebilir (Waite, 2008). Tenis oyuncularının duvarda farklı ritim antrenmanları ile performans düzeylerini geliştirilmeye yönelik çalışmada, ritim antrenmanlarına katılan tenis oyuncularının performanslarını anlamlı bir şekilde geliştirdiği görülmüştür (Söğüt, Kirazci and Korkusuz, 2012).…”
Section: Introductionunclassified